Neonatal surgical mortality in a Pediatric Surgical Centre with predicting risk factors - Obay A. Edan; Aws A. Al-hamdany; Sarmad Z. Al-dabbagh (Hygeia Press di Corridori Marinella, 2022)
Background: Many factors affect neonatal mortality; some could be manipulated while others are not. The upgrade and advancement in pediatric anaesthesia, the establishment of Neonatal Intensive Care Units (NICUs), the introduction of total parenteral nutrition, and practising fetal surgery, all improved the mortality rate. However, on the contrary, dealing with low birth weight, structural or chromosomal abnormalities, which are sometimes combined altogether, increase neonatal surgical mortality (NSM) rate. We present this study to detect the overall NSM in a Pediatric Surgery Centre at the tertiary level and predict some risk factors to guide intervention that improves the outcome. Methods: A retrospective study was conducted on 279 neonates with surgical conditions admitted to the Pediatric Surgery Centre in Al-khansaa Teaching Hospital (Mosul, Iraq) over 1 year (January 2019 to December 2019). The study evaluated the dependent (alive or dead) and independent variables (risk factors) that correlated to increased mortality. Result: According to the patient's outcome, the survival rate was 82.1% (229/279), while 17.9% (50/279) died. Factors identified as predictors of NSM were prematurity (p-value < 0.0001), low and very low birth weight (p-value < 0.0001), multiple operations (p-value = 0.039), NICU admission (p-value < 0.0001) and ventilator need (p-value < 0.0001). Digestive system anomalies constitute the most common surgical indication with the highest mortality rate. Conclusion: NSM in this study was comparably fair. Neonates with average gestational age and weight who had a single needed operation without ventilator support had the greatest probability for survival. We recommend the wise investment in advanced NICUs and the urgent need for another study to detect the burden of associated congenital anomalies on the mortality rate in the neonate to improve the outcome in low resources developing countries.